(untitled) (Research, Society and Development, 2022)
Introduction: the nurse is one of the professionals responsible for the management of care in the urgency and emergency sectors. Therefore, the present study aims to analyze the scientific productions about the leadership of nurses in urgency and emergency services. Methodology: This is a descriptive study, of the Integrative Literature Review (ILR) type, with a qualitative approach. The survey of articles took place during the period from June to July 2022. Results and Discussion: In the search for articles among the three databases, a total of 815 articles can be obtained, after applying the filters, 77 remained for analysis. After reading, analyzing and applying the inclusion and exclusion criteria, 09 articles remained to compose the final sample of this RIL. Nursing leadership is of paramount importance for achieving satisfactory results. The nurse is an essential professional in the context of emergency, where the quality of care provided by this professional is essential for health. Conclusion: Therefore, the nurse has a fundamental role in the management of urgency and emergency, presenting potentialities, such as the leadership and management of the nursing team.